Get live Maths 1-on-1 Classs - Class 6 to 12

Factorisation using common factors

Factorization by common factors

Ex 12.1, 1 (i)

Ex 12.1, 1 (ii)

Ex 12.1, 1 (iii) Important

Ex 12.1, 1 (iv) Important

Ex 12.1, 1 (v)

Ex 12.1, 1 (vi) Important

Ex 12.1, 1 (vii)

Ex 12.1, 1 (viii) Important

Example 2 Important

Example 1

Ex 12.1, 2 (i) You are here

Ex 12.1, 2 (ii) Important

Ex 12.1, 2 (iii)

Ex 12.1, 2 (iv) Important

Ex 12.1, 2 (v)

Ex 12.1, 2 (vi)

Ex 12.1, 2 (vii)

Ex 12.1, 2 (viii) Important

Ex 12.1, 2 (ix)

Ex 12.1, 2 (x) Important

Last updated at May 18, 2023 by Teachoo

Ex 12.1, 2 (Method 1) Factorise the following expressions. (i) 7x – 42 7x = 7 × x 42 = 2 × 3 × 7 7 is the only common factor. 7x − 42 = (7 × x) − (2 × 3 × 7) = 7 (x − (2 × 3)) = 7(x − 6) Ex 12.1, 2 (Method 2) Factorise the following expressions. (i) 7x – 42 7x − 42 = (7 × x) − (7 × 6) Taking 7 common = 7(x − 6)